An annotated checklist of the Indian species of the band-winged grasshopper genus Sphingonotus Fieber, 1852 (Orthoptera: Acrididae) with description of a new species - Gupta, Sunil Kumar; Chandra, Kailash; Husemann, Martin (Zootaxa, 2019)
Sphingonotus (Sphingonotus) changlangensis sp. nov. is a new species of Sphingonotus described from Namdapha National Park, Changlang District, Arunachal Pradesh, India. An annotated checklist of members of the genus Sphingonotus occurring in India is provided.